Development of Gatra Trigger National Resilience in Combating the Threat of Foreign Intelligence Covert Actions - Pujo Widodo; Moh Khusaini; Alfi Haris Wanto; Panji Suwarno; Vasyl Maliyk (PT. Islamic Research Publiser, 2026)
Developments in the global strategic environment indicate that threats to the state are no longer limited to conventional military conflicts but also encompass non-conventional threats, such as covert actions conducted by foreign intelligence agencies to influence a country's political, social, economic, and security stability. In this context, strengthening national resilience becomes a strategic instrument for identifying, anticipating, and addressing hidden and multidimensional threats. The analytical framework of national resilience in Indonesia employs the Astagatra approach, which consists of Trigatra (geography, natural resources, and demography) and Pancagatra (ideology, politics, economy, socio-culture, and defense and security) as the core elements shaping national resilience against various strategic threats. This research adopts a qualitative approach with a case study design. The findings reveal that the development of